Penggunaan Metode Titrasi Iodimetri Sebagai Pendukung Praktikum Biokimia: Membandingkan Kadar Vitamin C pada Varietas Cabai Merah Besar (Capsicum annum var. longum) dan Cabai Merah Keriting (Capsicum annum var. glabiusculum) - Kamaliah, Kamaliah (Jurnal Kompetensi, 2024)
Vitamin C is an essential vitamin that cannot be synthesized by the human body. Both large red chilies and curly red chilies contain Vitamin C, which can help meet human nutritional needs. This research aimed to assess the Vitamin C content in Big Red Chili (Capsicum annum var. longum) and Curly Red Chili (Capsicum annum var. glabiusculum) using the Iodimetric Titration method, serving as a practical application for Biochemistry lab activities. The results indicate that the Vitamin C content in Big Red Chili is lower than that in Curly Red Chili. The average Vitamin C content in Big Red Chili is 243.02, while in Curly Red Chili it is 384.06. The Iodimetric Titration Method is useful for testing Vitamin C levels in different chili varieties during Biochemistry practicum activities.